Introduction to biotechnology : - Herren, Ray V. (Thomson / Delmar Learning, 2003)
Introduction to Biotechnology : An Agricultural Revolution provides students with a basic understanding of the concepts that contribute to agriculture’s biotechnology revolution. Each chapter of this comprehensive text includes topics such as cell functions, genetics and genetic engineering, the uses of biotechnology and biotech careers. Also included is a thorough examination of the controversy and concerns over the use of genetic engineering, genetically modified organisms, cloning and their potential dangers to humans and the environments. This information enables students to engage and utilize the text’s science-based content in classroom discussions and research activities.